2024
DOI: 10.1039/d3cy01485a
|View full text |Cite
|
Sign up to set email alerts
|

Steering the electronic communication between Al/Ru bimetallic clusters in metal–organic framework composites for accelerating hydrogen evolution kinetics

Xueting Song,
Haifeng Yang,
Chenghua Zhang
et al.

Abstract: Synergistically modulating electron distribution between metal nodes in metal-organic frameworks (MOFs) is an effective strategy to improve the electrocatalytic performance of MOFs. Herein, a special bimetallic MOFs composite (Al0.35/Ru0.15-TCPP-CNTs) was...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…5a–c). 43 The d-band center ( ε d ) often dominates the progress of electrochemical reactions because it is directly related to the adsorption strength of the catalyst to reaction intermediates. According to the projected density of states (pDOS), it has been observed that attaching Co 3 O 4 on the TiO 2 surface tends to alter ε d (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…5a–c). 43 The d-band center ( ε d ) often dominates the progress of electrochemical reactions because it is directly related to the adsorption strength of the catalyst to reaction intermediates. According to the projected density of states (pDOS), it has been observed that attaching Co 3 O 4 on the TiO 2 surface tends to alter ε d (Fig.…”
Section: Resultsmentioning
confidence: 99%